Apposite macronutrient fertilization (AMNF) – an effective modus operandi for potato crop - KUMAR, PRINCE; SHARMA, JAGDEV; KUMAR, DIPAK; SHARMA, VINEETA; DUA, V K; SHARMA, ANIL; KUMAR, RAJ; KUMAR, MANOJ (The Indian Journal of Agricultural Sciences, 2021)
Potato is regarded as an important food crop, owing to its short duration, broader adaptability, nutritive supremacy and immediate returns. For getting more yields, farmers of Punjab are going for over fertilization of some nutrient and under fertilization of other which has resulted in inappropriate fertilization and consequently lower yields. Therefore, extension of adequate knowledge and awareness about these most important input components is utmost important for achieving optimum yield and better economic returns. So, the present investigation was initiated, during 2018-20 with the objective to reveal the extent of inappropriation of macronutrients followed in potato growing soils of Punjab. Information about average yield and fertilizer application rate was collected from 100 potato growing locations. Soils of all these locations were analyzed for various soil properties. It was observed that potato growers applied inappropriate amount of NPK. Application of more phosphorus (34.8-65.3 kg/ha) and less nitrogen (-68.4 to -85.8 kg/ha) and potassium (-38.3 to -66.8 kg/ha) has been practiced in these areas. The investigation further revealed that an increase in tuber yield (ranged between 2.04 to 4.51 t/ha) and consequently economic returns (₹15760-36020) can be achieved by following appropriate/recommended fertilization of macro nutrients.